Management of Giant Facial Neurofibroma With Intratumoral Hematoma in Neurofibromatosis Type 1 Patient. Issue 6 (September 2016) - Tak, Min Sung; Cho, Seong Eun; Kang, Sang Gue; Kim, Chul Han; Lee, Yong Seok
Abstract : Abstract: Type-1 neurofibromatosis, a common autosomal dominant disease, is also known as von Recklinghausen disease. Surgical procedures to treat this condition are challenging because of the brittleness of the surrounding blood vessels and soft tissues that bring the risk of causing fatal bleeding. With improvements in neurovascular embolization procedures, some literatures have been published about the application of preoperative embolization for neurofibromatosis. This case report describes a 60-year-old female with Type-1 neurofibromatosis, who presented giant facial neurofibromas with intratumoral hemorrhage on both cheeks. This patient demonstrates that these huge and challenging lesions can be successfully treated with preoperative embolization and surgical treatment. We also discuss the timing of surgical treatment with such lesions.